Relationship Between Service Quality and Patient Satisfaction in the Inpatient Room of Adventist Hospital Manado - Virginia Christy Porong; Suryadi N. N. Tatura; Novie H. Rampengan (CV. Inara, 2025)
This study investigates the relationship between service quality and patient satisfaction in inpatient wards at Adventist Hospital Manado, a leading private healthcare institution in North Sulawesi, Indonesia. Using the SERVQUAL model—which evaluates five dimensions of service quality: Tangibles, Reliability, Responsiveness, Assurance, and Empathy—the research aims to identify which dimensions most significantly influence patient satisfaction. A quantitative correlational design was employed, involving 95 respondents selected through purposive sampling from the Seiruni and Asteir inpatient wards, covering all hospitalization classes (Class 1–3, VIP, Silver, and Gold). Data were collected through structured questionnaires and analyzed using multiple linear regression via SPSS 25.0. Descriptive results indicated that Responsiveness received the highest average score, followed by Empathy and Assurance. The regression analysis revealed that Tangibles and Reliability had a statistically significant positive effect on patient satisfaction, while Responsiveness, Assurance, and Empathy, although positively correlated, did not reach significance. The model accounted for 74.3% of the variance in patient satisfaction (R² = 0.743), indicating strong explanatory power. These findings suggest that physical infrastructure, cleanliness, medical equipment, and consistency in care delivery are critical determinants of patient satisfaction. Although interpersonal aspects such as empathy and courtesy remain essential, patients prioritize visible service reliability and facility quality. The study underscores the importance of strategic improvements in operational consistency and hospital environment to enhance overall patient experience.